Entrepreneurial intention before and during COVID-19: A case study on portuguese university students - Lopes, João M. (2021)
The present research aims to compare the entrepreneurial intention of university students before and during the Covid-19 pandemic. For this purpose, some dimensions were analyzed, such as the availability of this target audience to undertake an activity at their own risk, the preference for a future while employed by others, their perception of the values that society places on en- trepreneurship, and the entrepreneurial abilities/skillsets. A comparative study of a quantitative nature was used, associating two samples composed of students of higher education in Portugal, the data were obtained before and during the COVID-19 pandemic. The analysis of the results permits us to conclude: (1) in the circumstances of macroeconomic changes resulting from the COVID-19 pandemic, entrepreneurial activity does not decrease; (2) respondents are less interested in being employed by others and more attracted to being entrepreneurs; (3) there is a growing concordance with the values that society places on entrepreneurship; and (4) there is now a greater aptitude for entrepreneurial activity. The present research is original, as it compares data obtained in different contexts of economic and social stability. It contributes to theory and practice, in the sense that it points to conclusions in the opposite direction of other studies carried out in situations of disasters of another nature, and can serve as a reference for the development of strategies to promote en- trepreneurship, within higher education institutions and official entities to publicize and promote new public policies.